Dietary soluble, insoluble, and total fiber intake and their dietary sources in association with breast cancer - Faezeh Zademohammadi; Bahareh Sasanfar; Fatemeh Toorang; Maedeh Mozafarinia; Amin Salehi-Abargouei; Kazem Zendehdel (BMC, 2024)
Abstract Background A few studies have examined the association between different types of dietary fiber as well as their sources and the risk of breast cancer (BC) and the present study aimed to investigate these associations in a case-control study among Iranian women. Methods A total of 464 women with pathologically confirmed breast cancer within the past year and 498 age-matched healthy controls were included. Dietary intakes were assessed using a 168-item food frequency questionnaire. The association between dietary soluble, insoluble, total dietary fiber, as well as, fiber from fruits, vegetables, legumes, cereals, and nuts intake with odds of breast cancer was assessed using multivariate logistic regression analysis. Results Mean total dietary fiber intake of patients with and without cancer were 33.1 ± 15.3 g per day (g/d) and 34.2 ± 16.5 (g/d), respectively. Dietary total fiber (OR = 0.65; 95%CI: 0.47-0.90, Ptrend = 0.01), insoluble fiber (OR = 0.68; 95%CI: 0.49-0.93, Ptrend = 0.01), fruits' fiber (OR = 0.68; 95%CI: 0.49-0.94, Ptrend = 0.02), and vegetables' fiber (OR = 0.66; 95%CI: 0.48-0.91, Ptrend = 0.01) were significantly associated with reduced likelihood of developing breast cancer in all participants. Furthermore, dietary total and insoluble fiber, as well as, fiber from fruits were significantly associated with lower odds of breast cancer in premenopausal women (P < 0.05). In contrast, cereals' fiber significantly increased the risk of breast cancer by 84% in premenopausal women (OR = 1.84; 95%CI: 1.18-2.86, Ptrend = 0.009). In postmenopausal women, cereals' fiber had a significant inverse association with odds of breast cancer (OR = 0.56; 95%CI: 0.31-1.03, Ptrend = 0.04). Also, fiber from vegetables was significantly associated with a lower risk of breast cancer in postmenopausal women (OR = 0.53; 95%CI: 0.30-0.94, Ptrend = 0.03). Conclusion Dietary fiber intake and more specifically insoluble, fruits', and vegetables' fiber intake might be associated with a reduced breast cancer risk, particularly in premenopausal women. Future prospective investigations are needed to confirm these findings.